Parthenium hysterophorus plant extract as an efficient green corrosion inhibitor for mild steel in acidic environment - Ji G.; Shukla S.K.; Dwivedi P.; Sundaram S.; Ebenso E.E.; Prakash R. (My University, 2025)
Asteraceae family - Parthenium hysterophorus plant leaves extract is reported as corrosion inhibitor of mild steel in HCl. Weight loss measurements, Tafel polarization and electrochemical impedancespectroscopy techniques are employed to analyze the effect on steel corrosion. A significant decreasein corrosion rate is observed using water extract of Parthenium hysterophorus plant as inhibitor. Themaximum potential of the extract was obtained at 1100 mg L-1 with 84% efficiency. It was found that adsorption of Parthenium hysterophorus extract follows Langmuir isotherm model. Mechanism of corrosioninhibition is explored with the help of UV-vis spectra and SEM images. © 2012 by ESG (www.electrochemsci.org).